PENGGUNAAN MEDIA INTERAKTIF BERBASIS GIMKIT DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Amellia Saputeri; Rahmadina Dina; Nur Aisya; Ahmad Suriansyah; Maimunah Maimunah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Natural and Social Sciences (IPAS) learning at SDN Sungai Lumbah 1 faces the problem of low student participation due to conventional methods. This study aims to evaluate the use of interactive media based on Gimkit as an innovative alternative in IPAS learning. The study was conducted at SDN Sungai Lumbah 1 with 27 teachers and grade 3 students as research subjects. The results of the study showed that the use of Gimkit was able to increase student motivation, interest, and involvement in learning, as well as create a more dynamic and collaborative classroom atmosphere. In addition, students found it easier to understand the material and showed better evaluation results than before. This study recommends the use of interactive media such as Gimkit as a relevant and enjoyable learning strategy, especially to support the learning needs of the digital generation in elementary school environments.